Model Hierarchies for Understanding Atmospheric Circulation. (23rd May 2019) - Maher, Penelope; Gerber, Edwin P.; Medeiros, Brian; Merlis, Timothy M.; Sherwood, Steven; Sheshadri, Aditi; Sobel, Adam H.; Vallis, Geoffrey K.; Voigt, Aiko; Zurita‐Gotor, Pablo
Abstract: In this review, we highlight the complementary relationship between simple and comprehensive models in addressing key scientific questions to describe Earth's atmospheric circulation. The systematic representation of models in steps, or hierarchies, connects our understanding from idealized systems to comprehensive models and ultimately the observed atmosphere. We define three interconnected principles that can be used to characterize the model hierarchies of the atmosphere. We explore the rich diversity within the governing equations in the dynamical hierarchy, the ability to isolate and understand atmospheric processes in the process hierarchy, and the importance of the physical domain and resolution in the hierarchy of scale . We center our discussion on the large‐scale circulation of the atmosphere and its interaction with clouds and convection, focusing on areas where simple models have had a significant impact. Our confidence in climate model projections of the future is based on our efforts to ground the climate predictions in fundamental physical understanding. This understanding is, in part, possible due to the hierarchies of idealized models that afford the simplicity required for understanding complex systems. Plain Language Summary: Model hierarchies are fundamental to our understanding of the large‐scale circulation of Earth's atmosphere. They have played a critical role in forming and testing our ability to simulate and predict the natural variability of the atmosphere, such as the variations of the extratropical jet streams, and for exploring how the climate will respond to external forcing, such as increased carbon dioxide. In this review we discuss simple models that form the basis of our understanding of the atmosphere and how they connect to the comprehensive models used for climate prediction through the model hierarchies. We describe three principles that help organize the model hierarchies and discuss benchmark models that have been influential in understanding the large‐scale circulation in the midlatitudes, middle atmosphere, and tropics. Key Points: Model hierarchies help address open research questions; we focus on how they have improved our understanding of atmospheric circulation Model hierarchies are commonly referred to but remain poorly defined; we identify three principles to organize models into hierarchies Key benchmark models of the atmospheric circulation are identified and connected to comprehensive models through model hierarchies